Assessment Of Nutritive Value In Milled Rice Grain Of Some Indian Rice Landraces And Their Molecular Characterization (Bangladesh Journal of Agricultural Research, 2011)
The study was aimed at the evaluation of nutritive values in terms of total protein and some essential amino acid content of a set of 258 diverse rice landraces maintained in the Germplasm Section of Indira Gandhi Agricultural University at Raipur, Chhattisgarh. Protein content of milled grains ranged from 4.91% to 12.08% with the mean of 6.63%. Similarly wide variation was recorded in lysine content which varied from 1.73 to 7.13 g/l6g N, the mean being 4.62 g/I6g N. Grain protein and lysine levels varied two to three folds. Variation for lysine content (CV 23.68%) was higher than that of protein content (CV 12.45%). This clearly indicated the existence of wide genetic variability for protein and lysine contents in rice. Two sets of ten elite lines each containing high levels of protein and lysine were further analyzed separately for another essential amino acid tryptophan. In the set with high protein, the tryptophan levels varied from 0.36-0.88 g/16 g N, the mean being 0.642 g/l6 g N. Among the landraces containing high levels of lysine, the tryptophan content ranged from 0.256 to 0.86 g/16 g N, the average being 0.514. A positive correlation of tryptophan with lysine content (r = 0.076) and a strong negative correlation with total protein content (r = - 0.923) were recorded. Donor lines for breeding rice varieties with optimum protein quality were identified as potential donor parents for genetic improvement of rice for nutritious grains. Fourteen SSR primer sets were used to investigate the level of polymorphism among the ten elite landraces of extra early maturity group. The estimated similarity ranged from 20.18 to 69.00% reflecting much variation at the DNA level. Keywords: Milled rice grain; protein; lysine; tryptophan; nutritive value of rice. DOI: http://dx.doi.org/10.3329/bjar.v36i3.9265 BJAR 2011; 36(3): 369-380